Pengenalan Citra Iris Mata Menggunakan Alihragam Wavelet Daubechies Orde 4 - Hartanto, Antonius Dwi; Isnanto, R. Rizal; Hidayatno, Achmad (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
Iris is a part of the circle around the eye pupil. Iris has a very unique pattern, different in each individual. On this basis the iris can be used as the basis for the introduction of biometrics. To identify the texture of the iris in an eye image, method of texture analysis can be used. There are several methods of texture analysis, one of which is to use a wavelet based on image feature extraction energy. The analysis uses the energy characteristics contained in wavelet transform. Based on that reason, in this research an application program to identify the iris of the eye based on Daubechies order 4 wavelet transform. Eye image used in this research was acquired and processed, beginning take on the characteristics and texture of the iris image which converted into polar form. Then the feature extraction is done using Daubechies wavelet transform order 4. The characteristics obtained is in the form of the energy value. The next stage is the recognition using nearest normalized Euclidean distance. Tests carried out in the research consist of four types: influence of sample database, influence of the decomposition level of Daubechies wavelet transform order 4, influence of different input image formats, and testing on eye images which are not in database. From the test results, it can be concluded that the highest recognition rate with the parameters shown in testing Daubechies wavelet transform order 4 level 4 with two samples iris image stored is 86.66%. The lowest recognition rate is shown in tests with Daubechies wavelet transform order 4 level 6 with one sample iris image stored is 62.5%. Then from the results of testing the influence of different input image formats, it can be concluded that the samples taken from 40 individuals which one sample is take for each person, use the format BMP as well as with use JPEG format. Whereas, from the test result for eye images which are not in database with threshold 0.3559, of the recognition level is 96%. Keyword : texture analysis, Daubechies wavelet transform order 4, iris, Euclidean distance